Where should electric vehicle users without home charging charge their vehicle?. (December 2022) - Jochem, Patrick; Gnann, Till; Anderson, John E.; Bergfeld, Moritz; Plötz, Patrick
Highlights: Curbside charging stations are still highly costly compared to other options. The need for curbside charging is often overestimated in literature. Charging possibilities at workplace and shopping facilities should be incentivized. Abstract: An often-heard argument against using plug-in electric vehicles (PEV) by urban dwellers is the missing curbside charging option. Some users are even expecting these charging stations to deliver cheap electricity. However, from an economic perspective several arguments speak against this hope and, furthermore, the need of curbside chargers is often exaggerated in literature. Consequently, we shed more light into these two hypotheses (H1. curbside charging is very costly and H2. there is hardly any need for curbside charging) and base our arguments on current and representative mobility data from Germany. Policymakers may focus stronger on charging offers at workplace or shopping facilities for achieving an efficient allocation of charging infrastructure.